Russian Girls Construct Freedom and Safety in Pandemic Times. Issue 3 (1st December 2020) - Zdravomyslova, Olga; Onegina, Elena
Abstract: In this article we analyse ten structured interviews with girls aged 15 to 19 from Moscow and St. Petersburg. We look at how the girls are dealing with the fundamentally new and dangerous situation created by the coronavirus pandemic and note that they are looking for a social and psychological space for themselves in which they can create and experience stability and safety. They are more concerned about security than ever before, while being, at the same time, very sensitive to restrictions on their freedom and agency. Girls' clear desire for privacy, fuelled by the pandemic's increasingly rapid invasion of their digital space, reinforces their urge towards agency and their understanding of freedom as autonomy.